2017
DOI: 10.7759/cureus.1213
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Caregiving on Various Aspects of the Lives of Caregivers

Abstract: ObjectiveThis study was designed to assess the impact of caregiving on the lives of the caregivers.MethodsA cross-sectional study was conducted between July and September 2015 at a teaching hospital in Karachi, Pakistan. Participants who were more than 18 years old and were involved in caregiving (former or current) of a family member were invited to participate in the study. The participants were recruited through consecutive sampling technique. A total of 400 caregivers were interviewed. Written informed con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 18 publications
5
22
0
Order By: Relevance
“…This might be because of the high rate of non-Saudi participants in this study who mostly have limited income and incur higher support expenses. Previous studies showed that a family caregiver of an adult patient with cancer who incurs higher expenditure on caregiving and has a lower monthly income showed a higher level of caregiving stress (13,33,37). This agrees with our findings.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This might be because of the high rate of non-Saudi participants in this study who mostly have limited income and incur higher support expenses. Previous studies showed that a family caregiver of an adult patient with cancer who incurs higher expenditure on caregiving and has a lower monthly income showed a higher level of caregiving stress (13,33,37). This agrees with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Older family caregivers had the lowest mean score for physical health and the highest mean score for caregiving stress. These values are consistent with previous studies among Pakistani, Hispanic and African American family caregivers (15,33). This study also found that lower levels of education were correlated to higher levels of caregiving stress.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations